2019
DOI: 10.3389/fpls.2019.01202
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Age-Related Developmental Leaf Senescence by the IAOx Pathway, PEN1, and PEN3

Abstract: Early age-related developmental senescence was observed in Arabidopsis cyp79B2/cyp79B3 double mutants that cannot produce indole-3-acetaldoxime (IAOx), the precursor to indole glucosinolates (IGs), camalexin and auxin. The early senescence phenotype was not observed when senescence was induced by darkness. The cyp79B2/cyp79B3 mutants had lower auxin levels, but did not display auxin-deficient phenotypes. Camalexin biosynthesis mutants senesced normally; however, IG transport and exosome-related pen1/pen3 doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Considering the astonishing leaf phenotypic variation in the Scalesia lineage, it is particularly interesting that we detected selection on potential regulators of leaf morphology, including genes well known to determine leaf cell number in A. thaliana (E2F1) 43 , 44 , cell fate in leaves (YABBY5) 45 , 46 , leaf senescence (RANBPM, LARP1C, PEN3) 47 49 , leaf variegation (THF1) 50 , 51 and leaf growth (PAC) 52 54 . It has been observed that Scalesia plants grown in shaded conditions, as opposed to the continuous direct light provided by their open Galápagos landscape habitats, show substantially retarded growth 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the astonishing leaf phenotypic variation in the Scalesia lineage, it is particularly interesting that we detected selection on potential regulators of leaf morphology, including genes well known to determine leaf cell number in A. thaliana (E2F1) 43 , 44 , cell fate in leaves (YABBY5) 45 , 46 , leaf senescence (RANBPM, LARP1C, PEN3) 47 49 , leaf variegation (THF1) 50 , 51 and leaf growth (PAC) 52 54 . It has been observed that Scalesia plants grown in shaded conditions, as opposed to the continuous direct light provided by their open Galápagos landscape habitats, show substantially retarded growth 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The classification of these genes into non-mutually exclusive categories showed 23 genes implicated in photosynthesis and leaf morphology/metabolism, 17 in stress response, 15 in fertility and reproductive organ function, 13 in life-phase transition and growth, 11 in the embryo, 10 in root functions, eight in immunity, seven in cellular functions (mitochondrial functions, cytoplasm, DNA repair, nucleus, cell elongation or autophagy), five in meiosis/mitosis, three in the vascular system, two in general metabolism, and one in methylation (Supplementary Information; Supplementary Table 07). As leaf morphology was an important innovation in the Scalesia radiation, it is particularly interesting that we found selection on potential regulators of leaf morphology, including genes well known to determine leaf cell number in A. thaliana (E2F1) (Oszi et al 2020; Berckmans et al 2011), cell fate in leaves (YABBY5) (Kojima et al 2011; Husbands et al 2016), leaf senescence (RANBPM, LARP1C, PEN3) (Crane et al 2019; Fu et al 2019; Zhang et al 2012), leaf variegation (THF1) (Ma et al 2015; Z. Wang et al 2016) , and leaf growth (PAC) (Jörg Meurer et al 2017; Holding 2000; J.…”
Section: Resultsmentioning
confidence: 99%
“…As GH3 is involved in IAA (indole-3-acetic acid) conjugation ( Staswick et al , 2005 ), we speculated that changes in IAA concentration might be a main factor regulating leaf senescence. The role of auxin in leaf senescence is complex ( Quirino et al , 1999 ; van der Graaff et al , 2006 ; Crane et al , 2019 ), and the potential mechanism is still much less understood. Higher concentrations of free IAA were detected in the senescent line than in the non-senescent line (our ongoing work); further studies on auxin conjugation are needed to better understand the mechanisms.…”
Section: Discussionmentioning
confidence: 99%